Recognition the Role of Traditional Villages in Tourism Development from The Legal Pluralism Perspective - Adnyani, Ni Ketut Sari; Wija Atmaja, Gede Marhaendra; Sudantra, I Ketut (International Journal of Social Science and Business, 2022)
The management of the diversity of traditions and culture in each region in the archipelago was born by the plurality of society with the characteristics of the various customary law systems as different from national law which can actually enrich the repertoire of Indonesian national law. The urgency of this article study is that there is a need for an integration of policies for the formation of regulations and management in the field of local wisdom such as customs and traditions found in each region in Indonesia. The problems studied are: first, to examine the policy of developing customs and traditions in the context of legal pluralism and second, to analyze the concept of law as an integrator in the policy of customs and traditions in the context of Indonesian legal pluralism. The results show that first, the development of customs and traditions in the context of legal pluralism so far, state law has been in an ordinate position and local wisdom has been in a subordinate position, while there has been marginalization of customary law community groups in the policy of developing customs and traditions; and second, the concept of law can function as an integrator between the interests of Â the sub-system in the policy of developing customs and traditions in the context of legal pluralism in Indonesia.